A Ka-band high-isolation waveguide power divider with planar output ports and out-of-phase. Issue 2 (8th March 2023) - Tang, Cong; Gao, Xin; Zhu, Hongquan; Zhang, Jinrong
Abstract: A waveguide power divider based on ridge waveguide to microstrip line transition is presented in this paper. To improve the isolation performance, a probe insulator is inserted into the contact face from the center of the waveguide side wall, also two chip resistors are mounted on a planar substrate and connected with the probe to absorb the coupled energy. The impedance transformation is accomplished by ridge waveguide to microstrip line transition, which is hidden in the waveguide. This proposed power divider shows merits of waveguide power dividers and substrate-integrated waveguide power dividers simultaneously, i.e. planar output ports, compact size, and high isolation. For verification, a power divider operating at the Ka-band is simulated, fabricated, and measured. The obtained results show the return loss and isolation are better than 10 and 20 dB, respectively. The measured insertion loss is <1.5 dB, including the insertion loss of waveguide to microstrip line transitions at the output port in the range of 34.6–39 GHz.